(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this research, we design a virtual library that allows users to have a 360-degree perspective and move freely. We will focus on the function of the library not only as ‘a public facility for lending books’ but also as ‘a place for encountering new knowledge by accident.’ In modern open-stack libraries, the function of ‘a place for encountering new knowledge by accident’ is realized through the act of ‘walking around’. However, regarding the online libraries and digital libraries, which have been rapidly developing in recent years, they offer scarce functionality of ‘encountering unknown knowledge by accident’ by ‘walking around in the library’, while increasing convenience through digitization.In light of this problem, this paper devises a virtual library equipped with the function that users can move freely in the library in a 360-degree view’. By providing the state of bookshelves and books which are on display by actual 360° videos rather than artifacts such as CG or animation, users can acquire necessary related information of books while having the realistic experience of being in the library. Past digital libraries are reproductions of libraries as building structures, and the libraries’ original function of encountering books and knowledge was low. On the contrary, as for the online libraries, users can only search for book information, and cannot obtain the sense of being in the library. This study proposes a new virtual library that combines past digital library and online library.